Health Assessment of Self‐employed Hairdressers in France. Issue 2 (3rd October 2014) - Deschamps, Frederic; Langrand, Jerome; Lesage, Francois‐Xavier
Abstract : Health Assessment of Self‐employed Hairdressers in France: Frederic DESCHAMPS, et al . Occupational Disease Department University Hospital of Reims, France— Objective: Hairdressers have a high incidence of occupational diseases, owing to excessive wet work and exposure to chemical substances. The objective of this study was to assess the prevalence of occupational diseases in a population of self‐employed hairdressers, matched for age and sex with a control group of wage‐earning hairdressers. Method: A health questionnaire was administered to both groups by an occupational health practitioner. Results: Irritative skin diseases were reported by 1.5% of the self‐employed hairdressers versus 9.1% of the wage earners. Conversely, the rates of respiratory diseases and cumulative musculoskeletal injuries were much higher among self‐employed hairdressers. Conclusions: This study shows that the overall health of self‐employed hairdressers is lower than that of their wage‐earning counterparts. This can be attributed to several aspects of work exposure, organization, including longer working hours, fewer protective measures and the absence of preventive medicine in the workplace.